How people learn : brain, mind, experience, and school - Brandsford, John D.; Brown, Ann L.; Cocking, Rodney R.; Pellegrino, James W.; Donovan, M. Suzanne (Washington, D.C. : National Academy Press, 2000)
Evaluates the most current scientific data on learning, teaching and learning environments. The objective of the book was to ascertain what is required for learners to reach deep understanding, to determine what leads to effective teaching and to evaluate the conditions that lead to supportive environments for teaching and learning. Six areas that are relevant to a deeper understanding of students' learning processes are explored: the role of prior knowledge in learning; plasticity and related issues of early experience upon brain development; learning as an active process; learning for understanding; adaptive expertise; and learning as a time-consuming endeavor. The book discusses research in another 5 areas that are relevant to teaching and environments that support effective learning: the importance of social and cultural contexts; transfer and the conditions for wide application of learning; subject matter uniqueness; assessment to support learning; and the new educational technologies.
Part I: Introduction..Learning: From speculation to sciencePart II: Learners and learning..How experts differ from novices..Learning and transfer..How children learn..Mind and brainPart III: Teachers and teaching..The design of learning environments..Effective teaching: Examples in history, mathematics, and science..Teacher learning..Technology to support learningPart IV: Future directions for the science of learning..Conclusions and recommendations for research
Str.285-348: Bibliografija
Str. 363-374: Kazalo
Keywords: učenje-psihologija; učenje-socijalni aspekti; učenje; podučavanje; obrazovna tehnologija; kurikulum; nastavnici; obrazovanje; teorija učenja; poučavanje; učitelji; tehnologija u obrazovanju